2001
DOI: 10.1038/sj.onc.1204885
|View full text |Cite
|
Sign up to set email alerts
|

PKCη enhances cell cycle progression, the expression of G1 cyclins and p21 in MCF-7 cells

Abstract: Protein kinase C encodes a family of enzymes implicated in cellular di erentiation, growth control and tumor promotion. However, not much is known with respect to the molecular mechanisms that link protein kinase C to cell cycle control. Here we report that the expression of PKCZ in MCF-7 cells, under the control of a tetracycline-responsive inducible promoter, enhanced cell growth and a ected the cell cycle at several points. The induced expression of another PKC isoform, PKCd, in MCF-7 cells had opposite e e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 60 publications
0
41
0
Order By: Relevance
“…The effects of PKC-Z on proliferation appear to be cell type specific. In this study using GBM cells, and another performed with epithelial breast adenocarcinoma MCF-7 cells (Fima et al, 2001), PKC-Z enhanced proliferation and cellcycle progression. However, studies using NIH3T3 cells and keratinocytes demonstrated inhibitory effects of PKC-Z on cell-cycle progression (Livneh et al, 1996;Ohba et al, 1998;Kashiwagi et al, 2000).…”
Section: Discussionmentioning
confidence: 78%
“…The effects of PKC-Z on proliferation appear to be cell type specific. In this study using GBM cells, and another performed with epithelial breast adenocarcinoma MCF-7 cells (Fima et al, 2001), PKC-Z enhanced proliferation and cellcycle progression. However, studies using NIH3T3 cells and keratinocytes demonstrated inhibitory effects of PKC-Z on cell-cycle progression (Livneh et al, 1996;Ohba et al, 1998;Kashiwagi et al, 2000).…”
Section: Discussionmentioning
confidence: 78%
“…PKC was found to participate in multiple processes involved in cell proliferation (2,12), differentiation (16), survival, and death (1). It was shown that the activity of PKC is regulated by phosphorylation/dephosphorylation events, interaction with small molecules (diacylglycerol and acid lipids), and ubiquitin-dependent degradation (13).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence accumulated in the last years points to distinct roles for individual PKC isozymes in the control of cell cycle progression, both at the levels of G 1 /S and G 2 /M transitions (2,3,28). Early studies in vascular endothelial cells have shown that phorbol esters potentiate the mitogenic effect of growth factors when added in early G 1 phase, but they inhibit DNA synthesis in late G 1 phase (22).…”
Section: Discussionmentioning
confidence: 99%
“…Phorbol esters, natural compounds that activate PKC and mimic the action of the lipid second messenger diacylglycerol, can impact on cell cycle progression both in positive or negative manners, resulting in either stimulation of mitogenesis or cell cycle arrest, or even in apoptosis, depending on the cell type (1)(2)(3)(4). Such a wide range of biological responses triggered by phorbol esters relates to the multiplicity of intracellular effectors for these compounds, which include the classic PKCs (␣, ␤I, ␤II, and ␥), the novel PKCs (␦, ⑀, , and ), as well as PKC-related kinases and nonkinase phorbol ester receptors (5,6).…”
Section: Activation Of Protein Kinase C (Pkc)mentioning
confidence: 99%